EFFICACY OF THE ETIS-2 COMPLEX PREPARATION IN THE TREATMENT OF SALMONELLOSIS PATHOGEN DISEASE - Djurakulov O.K (Western European Studies, 2025)
The article presents the results of testing the antibacterial efficacy of the drug ETIS-2 against the pathogen Salmonella Enteritidis in the body of 9 sheep
Keywords: ETIS-2 complex preparation; antibiotics; panacea; toxicity